Group contribution modeling of activity coefficients in associating solutions containing water, alcohols and carboxylic acids - Ferreira, Olga (2002)
A modified UNIFAC group contribution model for the prediction of activity coefficients in associating solutions (A-UNIFAC) is applied to calculate phase equilibria in binary and ternary mixtures of associating and non-associating species, including alcohols, water, carboxylic acids, esters, alkanes, aromatic hydrocarbons and alkyl chlorides. Self- and cross-association in these mixtures is adequately described by the definition of a single hydrogen-bonding group. The new model is able to give good predictions of vapor-liquid equilibria, liquid-liquid equilibria and infinite dilution activity coefficients, using a single set of group-interaction parameters.